Epidemiological Trends of Coronavirus Disease 2019 in Sierra Leone From March 2020 to October 2021 - Liu, Zhiguo; Gao, Liping; Xue, Chuizhao; Zhao, Chunchun; Liu, Tiezhu; Tia, Alie; Wang, Lili; Sun, Junling; Li, Zhenjun; Harding, Doris (Frontiers in Public Health, 2022)
Coronavirus disease 2019 (COVID-19), a serious public health challenge the world over, has led to significant health concerns in Sierra Leone. In the present study, epidemic indices, such as the number of cases, positivity rate, reproduction rate (R0), case fatality rate (CFR), age, and sex, were used to characterize the epidemiological trends of COVID-19. As of October 31, 2021, a total of 6,398 cases and 121 related deaths had been confirmed. The total number of COVID-19 reverse transcription polymerase chain reaction (RT-PCR) tests conducted to October 31, 2021, was 249,534, and the average positivity rate was 2.56%. Three waves of COVID-19 were recorded, occurring during weeks 15–46 in 2020 (2,369 cases), week 47 in 2020 to week 16 in 2021 (1,665 cases), and weeks 17–43 in 2021 (2,364 cases), respectively. Remarkably, there was no increase in the numbers of confirmed COVID-19 cases despite rising test numbers throughout the three waves. Moreover, three high R0 values were observed before each wave. The number of positive cases significantly correlated with positive numbers of international arrivals (P < 0.01), deaths (P < 0.01), and the positivity rate of tested samples (P < 0.01). Moreover, all of the deaths occurred during the peak of the three waves. Our results indicate that there was a low level of COVID-19 epidemic in Sierra Leone and that COVID-19's introduction led to local transmission. It is vital to fight against the spread of SARS-CoV-2 from the source of origin by strengthening testing and management of people entering the country. Our findings will provide important clues for expanding sample screening and will contribute to the reasonable allocation of medical resources.